POTENSI KOMBINASI EKSTRAK AKAR SIDAGURI (Sida rhombifolia L.) DAN GETAH JARAK (Jatropha curcas L.) SEBAGAI BAHAN DEVITALISASI - Maria Tanumihadja; Indrya Kirana Mattulada; Nurhayaty Natsir; Lukman Muslimin (Odonto : Dental Journal, 2019)
Background: Arsenic paste was used to devitalize dental pulp in some problems before surgical, but it has been proven to have many hazardous effects. So, other alternative drugs are needed that are equally effective but safer. Jatropha (Jatropha curcas L.) can cause lysis blood vessels in the pulp, whereas the sidaguri (Sidarhombifolia L.) are effective in relieving inflammation. The purpose of this study was to determine the devitalization effect of jatropha and sidaguri on rabbit animal model.Method: Sidaguri roots were extracted using reflux method while jatropha sap was dried using lyophilization method. For easy application, the extract made into a paste (1; 1) and inserted into the cavity. After 7 days of exposure, the teeth were removed, calcified and followed to histopathological staining and COX-2 expression (IHC).Result: Histopathological examination showed that the paste was able to cause necrosis of pulp nerve. Higher dose of the drug increased the necrosis area, but the paste is not able to reduce COX-2 expression.Conclusion: It can be concluded that the paste has a potential to developed as devitalization agent although it is necessary to study to the reduce the inflammation process.